Penerapan Concursus Realis dalam Tindak Pidana Pembunuhan Berencana dan Pemerkosaan Anak - Meliala, Farah Nabila Zahran; Sari, Diana Lukita; Zulfiani, Anita (Indonesian Publication Center, 2026)
This study aims to analyze the application of concursus realis in cases of premeditated murder accompanied by child rape, as well as to examine the sentencing in such circumstances. The research employs a normative juridical method with statutory and conceptual approaches. The results indicate that in judicial practice, concursus realis is applied when multiple independent criminal acts are committed by the same perpetrator within a single series of events. Normatively, Article 65 of the Indonesian Criminal Code stipulates that the sentence shall be based on the most severe punishment increased by one-third. However, in practice, judges do not always apply this mathematical calculation and may impose life imprisonment or even the death penalty by considering the severity of the crime, its impact, and aggravating circumstances. This discrepancy between normative provisions and judicial practice may lead to legal uncertainty. Therefore, stronger juridical reasoning is required in judicial considerations to ensure consistency and transparency in sentencing within the framework of concursus realis.